Fourier transform infrared spectroscopic study on glycoalkaloid concentration in varieties of solanum tuberosum - P.Nazni2, G. Velraj1, R.Ramya1* and (Journal of Experimental Sciences, 2011)
The potential of Fourier transform infrared spectroscopy used for predicting the concentration of glycoalkaloids in varieties of potato tuber, waxy and starchy (Solanum Tuberosum) was investigated in this study,a-solanine and a-chaconine are the main glycoalkaloids of potato tubers. Potato glycoalkaloids are the cholinesterase inhibitors and cause poisoning which is leading to accumulation of acytylcholine and even death. This will happen after consuming of potatoes with excessive glycoalkaloid level by human. One of the major factors affecting glycoalkaloid concentration in potato is its variety. In the present investigation the most popular varieties of potatoes waxy and starchy are subjected to FT-IR spectral analysis to determine the concentration of glycoalkaloid contents and the various nutrients. The implications of the results in terms of food safety are discussed.